Motivation, Organizational Culture, Human Resource Quality and Work Discipline on The Performance of Government Employees in Parangjoro Village, Grogol, Sukoharjo - Hardiman Hardiman; Istiatin Istiatin; Sudarwati Sudarwati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to determine the simultaneous (concurrent) and partial influence of the variables of Organizational Culture, Information Technology, Workload, and Supervision on employee performance at the Clinic.Sportin Cibubur. This study uses a quantitative descriptive approach. A Likert scale is also included to measure organizational culture, informatics techniques, workload, and supervision on the performance of sports clinic employees in Cibubur. This study took place at the sports clinic on Jl. Jambore No. 1, Cibubur, East Jakarta. This study took four months, from December 2025 to March 2026, starting from observation to data collection and research conclusions. The population of this study was all 85 employees of the Cibubur sports clinic. The sample size was 85 employees. The sampling technique used in this study was saturated sampling, meaning that all populations were sampled in the study. After data tabulation, the data were processed using multiple linear regression analysis tools with SPSS 27 software. The results showed that there was a partial and simultaneous influence of the variables Organizational Culture, Information Technology, Workload, and Supervision on employee performance at the Cibubur Sports Clinic.Sportin Cibubur